English for Religious Purposes: The Specific Purposes of Islamic University Students in Indonesia in Learning English - Paidi Gusmuliana; Safnil Safnil; Syafryadin Syafryadin; Kodarni Kodarni (Journal of Innovation in Educational and Cultural Research, 2023)
In the past, English was considered the language of non-Islamic religions but now English is believed to be the language for international communication for academic and 'dakwah' purposes. However, students of Islamic universities and institutes may have various purposes for learning English. This is because young scholars may have not seen the real need to study English outside the campus and this is not introduced by their teachers when they study at high schools. This study is aimed at describing the main purposes of learning English as a foreign language perceived by the students of Islamic Institutes and Universities in Indonesia. Seven hundred and fourteen undergraduate students from three different Islamic institutes were involved in this study. The finding shows that the primary objective of students learning English at these three institutions is to serve as a conduit for promoting the faith of Islam and to be able to convey Islamic teachings on a larger (international) basis Furthermore, these students stated that their religious goal in learning English was to be able to improve their English language skills while also receiving a lot of Islamic knowledge, even in the form of English material delivered concretely.